Techno-Economic Analysis of Fuel Switching from Coal to Natural Gas for NPK Fertilizer Drying Process - Rizal Arifin; Devi Intan Silviani; Rakhma Ayu Giarti; Daril Ridho Zuchrillah (IPTEK The Journal of Engineering, 2026)
Using coal as the primary fuel in the NPK fertilizer industry contributes significantly to carbon dioxide (CO₂) emissions, which negatively impact the environment and hinder the achievement of national decarbonization targets. To address this, this project aims to evaluate the technical and economic feasibility of switching from coal to natural gas in the furnace unit of the NPK fertilizer production process. As demands for efficiency and sustainability increase, the evaluation of fuel switching to natural gas is underway. This project re-simulates the combustion process in the furnace using Aspen Plus V14. Evaluation is carried out on thermal performance, CO₂ emissions, and economic indicators, including Capital Expenditure, Operational Expenditure, NPV, IRR, and Payback Period. The results show that natural gas achieves a thermal efficiency of 90.11%, reduces CO₂ emissions by 27.5% compared to coal, and yields a favorable economic value: NPV of $76,009.13, IRR of 32%, and Payback Period of 3 years. Based on these results, natural gas is considered a balanced fuel option from technical, environmental, and economic perspectives. It is feasible to implement as an energy transition strategy in the NPK fertilizer industry.